Has the prevalence of malnutrition and obesity in children from North Korean refugee families improved after resettlement in South Korea? A longitudinal cohort study - So-Yeong Kim; Seong-Woo Choi (BMJ Open)
Objectives This study assessed changes in the prevalence of malnutrition and obesity in children from North Korean (NK) refugee families resettling in South Korea (SK).Design A longitudinal cohort study.Setting This study, conducted between 2017 and 2023, recruited participants through snowball sampling using local Hana Centres, alternative schools, religious organisations, civic groups, and other community-based networks.Participants Of the 441 children initially recruited, 406 participated in the baseline survey after excluding 35 with missing height or weight data. Among them, 187 (46.1%) completed a follow-up survey conducted at least 1 year later.Primary outcome measures The prevalences of stunting, underweight, wasting and obesity were defined according to the 2017 Korean National Growth Chart: stunting as height-for-age below the third percentile, underweight as weight-for-age below the fifth percentile, wasting as weight-for-height below the fifth percentile for ages 0–23 months or body mass index (BMI)-for-age below the fifth percentile for ages 2–18 years and obesity as BMI-for-age at or above the 95th percentile for ages 2–18 years.Results The prevalence of stunting was 7.5% at baseline and 5.4% at follow-up, while those of underweight and wasting were 6.4% vs 5.4% and 11.2% vs 5.9%, respectively; however, none of these changes were statistically significant. In contrast, the prevalence of obesity increased significantly from 11.1% at baseline to 18.8% at follow-up (p=0.045).Conclusion Despite residing in SK for an extended period, children from NK refugee families continue to experience malnutrition, while the prevalence of obesity is rising significantly.